Analysis on swarm robot coordination using fuzzy logic - Ade Silvia Handayani; Siti Nurmaini; Irsyadi Yani; Nyayu Latifah Husni (Institute of Advanced Engineering and Science, 2019)
In this paper, coordination among individual of swarm robot in communicating to maintain the safe distance between robots was analyzed. Each robot coordinates their movements to avoid obstacles and moving simultaneously. Evaluation of swarm robot performance is analyzed in this paper, namely: the coordination among robots to share information in safe distance determination. In controlling the coordination of motion, each robot has a sensor that provides several inputs about its surrounding environment. Fuzzy logic control in this paper allows uncertain input, and produces unlimited commands to control motion direction with speed settings according to environmental conditions. In this experiment, it is obtained that the size of the environment affects the coordination of robots.